Mass spectrometric investigation of alamethicin - Marik, Tamás (Acta Biologica Szegediensis, 2013)
The peptaibols, such as alamethicin are secondary metabolites belonging to the family of fungal peptide antibiotics. These compounds are linear, amphipathic oligopeptides classified into 4 subfamilies and composed of 5-20 amino acids. Their backbones usually contain several nonproteinogenic amino acid residues representing characteristic building blocks of the structure. In our present work, the mass spectrometric analysis of alamethicin has been investigated by on-line reversed-phase high performance liquid chromatography (HPLC) coupled to electrospray ionization tandem mass spectrometry (ES-MS). Initially, the parameters of the MS were optimized by the continuous infusion of an alamethicin standard solution directly into the ESI source. Then, the proper HPLC method was developed for the analysis of the alamethicin components, which was capable to separate the peaks of F50-5, F50-6a, F50-7 and F50-8b from each other, which could be identified based on their mass spectra.